2003
DOI: 10.1002/jat.923
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological evaluation of an electrically heated cigarette. Part 1: Overview of technical concepts and summary of findings

Abstract: This series of papers provides a description of the toxicological evaluation of an electrically heated cigarette (EHC). With this novel cigarette design the tobacco is heated by a series of electric heating elements, which allows for greater control of the available heat and results in lower temperatures and less combustion compared with conventional lit-end cigarettes. This design was subjected to testing, including an evaluation of smoke chemistry, in vitro bacterial genotoxicity, in vitro mammalian cell cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 27 publications
3
45
0
1
Order By: Relevance
“…950°C for the 1R4F to ca. 600°C for the EHC (Patskan and Reininghaus, 2003) qualitatively and quantitatively alters the smoke composition (Fig. 3B).…”
Section: Discussionmentioning
confidence: 93%
“…950°C for the 1R4F to ca. 600°C for the EHC (Patskan and Reininghaus, 2003) qualitatively and quantitatively alters the smoke composition (Fig. 3B).…”
Section: Discussionmentioning
confidence: 93%
“…A promising approach to decrease such risk is the reduction of the concentrations of combustion-derived constituents in CS without modifying the amount of delivered nicotine. Heating rather than combusting tobacco has been shown to substantially reduce the amounts of constituents in CS (Patskan and Reininghaus, 2003). In a 28-day rat inhalation model, we previously showed that exposure to aerosol from a carbon-heated tobacco product significantly reduces its effects on the respiratory tract of rats compared with those of burning tobacco from the reference cigarette, 3R4F (Kogel et al, 2014).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%
“…40 mg vs. 770 mg) (Patskan & Reininghaus, 2003). The EHCSS (5 mg tar, 0.3 mg nicotine, and 0.6 mg CO according to the International Standards Organization [ISO]) was used for simulations 1-4 and Marlboro (6 mg tar, 0.5 mg nicotine and 7 mg CO according to ISO) cigarettes for simulations 5-8.…”
Section: Test Cigarettesmentioning
confidence: 99%